Trends and Emerging Themes in Halal Tourism Studies: A Bibliometric Review Using VOSviewer - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of halal tourism research using VOSviewer to identify trends, thematic developments, and collaboration patterns within the academic literature. Drawing on a dataset of publications indexed in Scopus between 2000 and 2024, the study maps co-authorship networks, country collaborations, keyword co-occurrences, and temporal shifts in research focus. The findings reveal that halal tourism is an emerging and rapidly expanding field, with Indonesia and Malaysia leading in scholarly output and international partnerships. Core research themes have traditionally centered on tourist satisfaction, behavioral intention, and service quality, but recent developments indicate a shift toward sustainability, digital engagement, and Islamic marketing. The overlay and density visualizations highlight both mature themes and underexplored areas, suggesting future research opportunities in ecotourism, decision-making processes, and the qualitative dimensions of Muslim travel experiences. This study contributes to a deeper understanding of the intellectual structure of halal tourism and provides strategic insights for scholars, policymakers, and industry stakeholders in advancing the field.